Didactic use of mathematizing games through graphs. an experience - Jorge Martín Morales; José María Muñoz Escolano; Antonio M. Oller Marcén (Universidad de La Rioja, 2013)
In this paper we suggest an activity that allow students of different educational levels (from secondary school to higher education) to comprehend and apply modelling processes. Specifically, some educational mathematical games are modelled using basic notions of graph theory in order to solve several questions related to the analysis of such games.